A Food‐Effect Study to Evaluate the Oral Bioavailability of Desidustat. Issue 4 (2nd December 2022) - Patel, Hardik; Momin, Taufik; Kansagra, Kevinkumar; Patel, Harilal; Shah, Chintan; Barot, Ajaykumar; Bhavsar, Jay; Zala, Kuldipsinh; Parmar, Deven
Abstract: This randomized, single‐treatment, 2‐sequence study evaluated the food effect on oral bioavailability of desidustat. Healthy adult male and female subjects were enrolled and randomly assigned to receive desidustat 50 mg orally in a fasting state in one period and a fed state in the other period. A standardized high‐fat, high‐calorie breakfast was served to assess the food effect. The pharmacokinetic results showed that the time to maximum blood concentration of desidustat was delayed significantly ( P  < .0001) in the fed state compared to the fasting state. The ingestion of food decreased the maximum blood concentration (Cmax ) compared to the fasting state (mean Cmax, 3248 ng/mL in the fed state vs 5496 ng/mL in the fasting state). The geometric mean ratio of fed/fasting for log‐normal (ln) Cmax was 57. The exposure decreased in the fed state compared to the fasting state (mean area under the concentration‐time curve [AUC] over the dosing interval, 25 559 ng  h/mL in the fed state versus 33 705 ng  h/mL in the fasting state; mean AUC from time 0 to infinity [AUC0‐∞ ], 25, 910 ng  h/mL in the fed state vs 34 233 ng  h/mL in the fasting state). The geometric mean ratio of fed/fasting for lnAUC from time 0 to the last quantifiable concentration and ln AUC0‐ ∞  was 77 and 76, respectively. The 90%CI of fed/fasting ratio of the geometric mean of lnCmax, AUC over the dosing interval, and AUC0‐∞ of desidustat 50 mg did not fall within 80%–125% margin. Therefore, the absence of food effect could not be established. It can be inferred that food has a significant effect on the oral absorption of desidustat. Therefore, food must not be consumed 1 hour before and 2 hours after the oral administration of desidustat.